2008
DOI: 10.1063/1.2927871
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the dynamic transition in proteins

Abstract: Despite extensive efforts in experimental and computational studies, the microscopic understanding of dynamics of biological macromolecules remains a great challenge. It is known that hydrated proteins, DNA and RNA, exhibit a so-called "dynamic transition." It appears as a sharp rise of their mean-squared atomic displacements r2 at temperatures above 200-230 K. Even after a long history of studies, this sudden activation of biomolecular dynamics remains a puzzle and many contradicting models have been proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
213
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(245 citation statements)
references
References 32 publications
28
213
4
Order By: Relevance
“…4, which we concluded must be due to the dynamics of the interfacial water since it is basically universal and present also in solid systems with only water molecules moving on the given time-scale, has also been suggested [37] to mainly arise from protein dynamics. Although fast local protein dynamics occurs on a similar time-scale as the main water process the small dielectric constant of a protein (ɛ ≈ 2-4) compared to that of water (ɛ ≈ 80 at room temperature) should ensure that the protein contribution to the dielectric relaxation process is minor compared to Fig.…”
Section: Discussionmentioning
confidence: 96%
“…4, which we concluded must be due to the dynamics of the interfacial water since it is basically universal and present also in solid systems with only water molecules moving on the given time-scale, has also been suggested [37] to mainly arise from protein dynamics. Although fast local protein dynamics occurs on a similar time-scale as the main water process the small dielectric constant of a protein (ɛ ≈ 2-4) compared to that of water (ɛ ≈ 80 at room temperature) should ensure that the protein contribution to the dielectric relaxation process is minor compared to Fig.…”
Section: Discussionmentioning
confidence: 96%
“…For example, it has been reported that the transition is coupled to the onset of translational motions in hydration water [47][48][49]. In addition, it has been debated whether the transition is a real phenomenon, or merely a manifestation of the fact that the measurable atomic dynamics enter the experimentally accessible resolution window above certain temperatures [17,18,24,25,27]. In such a scenario, the dynamic motions of the biomolecules may increase without any discontinuity.…”
Section: Resultsmentioning
confidence: 99%
“…Since secondary β-relaxation processes exist also in the bulk solvent, the fluctuations localized in the hydration shell of the protein are classified as β h -relaxation and are expected to carry the dynamics distinct from the bulk [25]. The dynamical transition then occurs when the β hrelaxation of the hydration shell slows sufficiently down, with lowering temperature, to become longer than the instrumental time-scale (dynamical freezing) [26,27].…”
Section: Introductionmentioning
confidence: 99%